Protesting parents as a significant social and educational phenomenon: Andragogical inspirations - Szczygiel, Premyslaw (International Journal about Parents in Education, 2023)
The aim of this paper is to give the initial analysis of the phenomenon of protesting parents within a wider study on the learning potential of rebellion. This thread appeared due course the induction of the category “socialization to rebellion” from the empirical material. In this research project, the author uses a biographical perspective proposed by Danuta Urbaniak-Zając. The empirical material is analysed in a “transverse” way. First, individual biographies are analysed. Then all empirical material is compared with respect to differences and similarities. In the narrations of the “rebellious” people several threads about their childhood and participation in protests along with their parents were discovered. The analysed narrations show that protesting parents could potentially have played an important role in shaping the involvement of respondents in social and political affairs. It can be seen as an important citizen education issue.